The Santa Rosa exchange a tri-juntion of Santa Rosa's I.T., student, and residential communities - Bautista, Regine C. (College of Architecture, University of the Philippines Diliman, 2018)
Santa Rosa has always been known to be a tourist destination for recreation and shopping in the past few years, there has also been an increase in residential developments in the southwest part of the city, resulting in a student-population growth. Apart from being a tourist go-to-place, what most people don't know about is the promising Information Technology industry of Santa Rosa. As a city that seeks to develop its industrial sector and improve its employment rate, and as the site of the "University Belt of the South", there is a need for a central venue that addresses the needs of I.T. professionals and students. This central venue shall also house an I.T. skills development center as project under Santa Rosa's Manpower Training Center. This study proposes The Santa Rosa Exchange, an architectural project that shall help answer Santa Rosa's need for a central venue for its I.T. and student communities. This book shows how The Santa Rosa Exchange is produced through a comprehensive research including the context of Santa Rosa, a thorough analysis of the site, and a formulation of appropriate design objectives and required programming.